PHOTOMETRICAL STUDY OF CLOSE BINARY SYSTEM V841 Cyg - Sergienko, O. G.; Bodryagin, D. V.; Panko, E. A. (Одеські астрономічні публікації, 2013)
We present the results of research of scantily explored close binary system V841 Cyg with possible period variations. It was attributed as /3 Lyr and as near contact binary star. We obtained light curve of the star in July 2013 in V-band. Both eclipses are partial, the depths of primary and secondary minima are 0m.53 and 0m.20. Light curve has feature near primary minimum: practically horizontal parts in phases ±(0.1 — 0.16). We found new time minima: HJDI = 2456504.48122, BJDH = 2456493.44562. We obtained new parameters of binary system using Binary Maker 3 package. The system contains from A6 V+G5 V stars with mass ratio about 0.49. The components have temperatures TeffI = 8550°, TeffI = 5500° and estimated masses MI = 1.85, MII = 0.90; they fill own Roshe lobes on 95% and 92% correspondingly and both components are deformed. The distance between components is about 5R©, the distance between component surfaces is about 1.4R©. We confirm the V841 Cyg classification as is NCB system, with not significant mass transfer.